Validation of auditory detection response task method for assessing the attentional effects of cognitive load. (4th July 2018) - Stojmenova, Kristina; Sodnik, Jaka
ABSTRACT: Objectives : There are 3 standardized versions of the Detection Response Task (DRT), 2 using visual stimuli (remote DRT and head-mounted DRT) and one using tactile stimuli. In this article, we present a study that proposes and validates a type of auditory signal to be used as DRT stimulus and evaluate the proposed auditory version of this method by comparing it with the standardized visual and tactile version. Methods : This was a within-subject design study performed in a driving simulator with 24 participants. Each participant performed 8 2-min-long driving sessions in which they had to perform 3 different tasks: driving, answering to DRT stimuli, and performing a cognitive task (n-back task). Presence of additional cognitive load and type of DRT stimuli were defined as independent variables. DRT response times and hit rates, n-back task performance, and pupil size were observed as dependent variables. Results : Significant changes in pupil size for trials with a cognitive task compared to trials without showed that cognitive load was induced properly. Each DRT version showed a significant increase in response times and a decrease in hit rates for trials with a secondary cognitive task compared to trials without. Similar and significantly better results in differences in response times and hit rates were obtained for the auditory and tactile version compared to the visual version. There were no significant differences in performance rate between the trials without DRT stimuli compared to trials with and among the trials with different DRT stimuli modalities. Conclusions : The results from this study show that the auditory DRT version, using the signal implementation suggested in this article, is sensitive to the effects of cognitive load on driver's attention and is significantly better than the remote visual and tactile version for auditory–vocal cognitive (n-back) secondary tasks.